Antecedents of Tax Compliance of Small Business Enterprises: a developing country perspective - Sadress, Night; Bananuka, Juma; Orobia, Laura; Opiso, Julius (International Journal of Law and Management, 2019)
The purpose of this study was to investigate the contribution of attitude towards electronic tax system, adoption of electronic tax system and isomorphic forces to tax compliance of Small Business Enterprises in a developing country in a single study. Design/ methodology - This study is cross sectional and correlational. Data were collected through a questionnaire survey of 214 owner managed Small Business Enterprises in Uganda through their managers. Data were analyzed using Statistical Package for Social Sciences. Findings – Attitude towards electronic tax system, adoption of electronic tax system and isomorphic forces significantly contribute to tax compliance to the extent of 57.4%. Isomorphic forces has a high predictive power of tax compliance as compared with attitude towards electronic tax system. Further, coercive, normative and mimetic isomorphism as constructs of isomorphic forces are significantly associated with tax compliance. Research limitations / implications– Given that this study was cross sectional, monitoring changes in behaviour over time was not possible. The results are useful for policy makers and tax payers in developing countries. These results can also be generalized to other developing countries especially those in Africa and other continents dominated by developing countries. Originality / Value–To the researchers’ knowledge, this is the first study to examine the contribution of attitude towards electronic tax system, adoption of electronic tax system and isomorphic forces to tax compliance of small business enterprises in a developing country in a single study on the African scene.
Keywords: Adoption of electronic tax system; Isomorphic forces; Theory of reasoned action; Institutional theory; Technology Acceptance Model